Dillon King: capstone - King, Dillon, artist (Colorado State University. Libraries, 2022)
The artist's statement: My name is Dillon King and I'm a photographer. My focus is based around the narrative or the storytelling ability an image has. I use a combination of elements including color and complex composition to assist the viewer in finding an emotive response. A few artists I look towards are Nan Goldin, Gordon Parks, Gregory Crewdson, Robert Capa, and Eddie Adams for their ability to show stories. With the age of social media, we are fed images over and over again that are shallow in both focus and meaning. While a shallow focus, used properly, has the ability to show us the depths of emotion, I chose to primarily use a wider range of focus to bring in more elements for storytelling. If the image contains a human figure, we are given more potential narrative with every new object we can see clearly. Within an image that doesn't contain a human figure, I aim to give enough information for deduction of the objects interplay within the frame. I choose to primarily use digital image capturing as it gives more potential for color. Color, a primary focus of my artistic technique, has a profound ability to direct a story due to its association with emotion. Digital gives me more manipulatable information to begin with. My focus is based around the storytelling ability an image has. I use a combination of elements including color and complex composition to assist the viewer in finding an emotive response, leading the audience to fabricate a story for themselves. Each image is intentionally unrelated for this reason.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making